2018
DOI: 10.1515/cclm-2017-0905
|View full text |Cite
|
Sign up to set email alerts
|

Screening for connective tissue disease-associated antibodies by automated immunoassay

Abstract: The positive predictive value for AASRD was higher for EliA than for IIF, but, depending on the disease, EliA might fail to detect antibodies that are detected by IIF. Combining immunoassay with IIF adds value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 19 publications
6
36
0
Order By: Relevance
“…This is in line with recent studies that showed that combining an immunoassay with ANA IIF adds value if the results of both tests are correctly judged in the context of the clinical manifestations of the patient (42,43). Furthermore, combining IIF with a solid-phase assay can assist in patient strati cation, especially in case of a low-positive ANA IIF titer (42,44,45). ICAP promotes to integrate the ANA IIF titer and pattern with advice for follow-up testing, taking into account the clinical presentation of the patient (10,46).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with recent studies that showed that combining an immunoassay with ANA IIF adds value if the results of both tests are correctly judged in the context of the clinical manifestations of the patient (42,43). Furthermore, combining IIF with a solid-phase assay can assist in patient strati cation, especially in case of a low-positive ANA IIF titer (42,44,45). ICAP promotes to integrate the ANA IIF titer and pattern with advice for follow-up testing, taking into account the clinical presentation of the patient (10,46).…”
Section: Discussionsupporting
confidence: 89%
“…Clinicians and laboratory professionals considered that combined information on HEp-2 ANA and speci c tests for anti-ENA and anti-dsDNA antibodies is most informative. This is in line with recent studies that showed that combining an immunoassay with ANA IIF adds value if the results of both tests are correctly judged in the context of the clinical manifestations of the patient (42,43). Furthermore, combining IIF with a solid-phase assay can assist in patient strati cation, especially in case of a low-positive ANA IIF titer (42,44,45).…”
Section: Discussionsupporting
confidence: 85%
“…We evaluated the performance of ANA for SLE diagnosis on 9851 unique consecutive patients tested for ANA (for description of the population, see Willems et al 7). All patients were tested for ANA by IIF (HEp-2000; ImmunoConcepts) and by solid-phase assay (EliA CTD screen; Thermo Fisher) 7.…”
mentioning
confidence: 99%
“…We evaluated the performance of ANA for SLE diagnosis on 9851 unique consecutive patients tested for ANA (for description of the population, see Willems et al 7). All patients were tested for ANA by IIF (HEp-2000; ImmunoConcepts) and by solid-phase assay (EliA CTD screen; Thermo Fisher) 7. The clinical diagnosis was documented for 2475 patients, including (1) all patients who tested positive for IIF (cut-off 1:80) and/or CTD screen (cut-off ratio 0.7) and (2) a selection of 500 patients who tested double negative (including 150 patients with IIF titre 1:40) 7.…”
mentioning
confidence: 99%
“…Indeed, the probability of identifying anti‐dsDNA and antibodies to extractable nuclear antigens increases with increasing ANA titres 2. Overall, the higher the antibody level, the higher the probability of an ANA-associated systemic rheumatic disease (AASRD) 3–5…”
mentioning
confidence: 99%